ANALISIS FAKTOR KEPATUHAN TERHADAP MANAJEMEN PENATALAKSANAAN PENYAKIT HIV/AIDS : LITERATURE REVIEW - Rismauli; Indriati Kusumaningsih (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Adherence to disease management among HIV/AIDS patients is a key factor in the success of antiretroviral (ARV) therapy. Adherence remains a challenge due to individual factors and the healthcare environment. Objective: To analyze the factors associated with HIV/AIDS adherence to disease management. Methods: This study employed a literature review approach. Involving seven qualitative or quantitative articles regarding adherence factors where the research subjects are HIV/AIDS patients.Data analysis was conducted using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA). Results: The results of the study indicate that there is a relationship between patient individual factor,social factor,and health care system with patient adherence to HIV/AIDS management (p < 0.05).